2021
DOI: 10.1016/j.sjbs.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical adaptations and ionic homeostasis in aquatic halophyte Cyperus laevigatus L. Under high salinities

Abstract: Salinity is extremely hazardous to agriculture worldwide and its expanding constantly. Soil of almost 100 countries facing salinity problem including Pakistan. Cyperus laevigatus also act as salinity indicator species is a naturally adapted halophyte dispersed in subtropical regions of world. Six populations of C. laevigatus were collected from different saline habitats to evaluate adaptations regarding anatomical and physiological characteristics. C. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…Water deficit environments are generally known to initiate oxidative stress in plants by the production of extra reactive oxygen species (ROS) [61][62][63] and antioxidative enzymes that play a protective role in reducing the metal toxicity by scavenging ROS [64][65][66]. Previously, it was shown that drought stressed conditions increased ROS production in cells/tissues, which were then scavenged by the activities of antioxidant compounds [56,65,67].…”
Section: Discussionmentioning
confidence: 99%
“…Water deficit environments are generally known to initiate oxidative stress in plants by the production of extra reactive oxygen species (ROS) [61][62][63] and antioxidative enzymes that play a protective role in reducing the metal toxicity by scavenging ROS [64][65][66]. Previously, it was shown that drought stressed conditions increased ROS production in cells/tissues, which were then scavenged by the activities of antioxidant compounds [56,65,67].…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, aquifers have already been exhausted due to injudicious consumption of groundwater for irrigation purpose to produce crops and fodder [12][13][14]. So, there is a need to investigate some approaches to reduce the necessity of potable water in this sector.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of metal accumulation, a large number of active free oxygen radicals are formed, which may be the main cause of cell membrane lipid peroxidation, and this also harms the functioning and structure of the cell membrane [76][77][78]. Excessive reactive oxygen species (ROS) production causes oxidative stress, as reported for many crops under heavy metals treatment, and is likely to be commenced by molecular oxygen excitation (O2), to generate singlet oxygen, or by electron transfer to O2 and the genesis of free radicals, i.e., O 2− and OH − [79][80][81]. Plant response to oxidative stress also depends upon plant species and cultivars, and this ROS production in plants is removed by a variety of antioxidant enzymes such as SOD, POD, CAT, and APX [82,83].…”
Section: Discussionmentioning
confidence: 99%